2006
DOI: 10.1016/j.ijdevneu.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic property of geniposide for inducing the neuronal differentiation of PC12 cells

Abstract: The emerging data show that the insulinotrophic hormone glucagon-like peptide-1(GLP-1) and its agonist extendin-4 have neurotrophic function to inducing neuronal differentiation of PC12 cells and prevent neurons damage challenged by oxidative stress. Here, with the model of high throughput screen for GLP-1 receptor agonists, we screen and identify that geniposide is a novel agonist for GLP-1 receptor. Furthermore, geniposide induces the neuronal differentiation of PC12 cells with resulting neurites outgrowth; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 20 publications
2
61
0
Order By: Relevance
“…9) Our previous works showed that geniposide was a novel agonist for glucagon-like peptide 1 receptor (GLP-1R), which induced the neuronal differentiation of PC12 cells and prevented PC12 cells from oxidative stress. [10][11][12] However, the mechanisms involved in these cytoprotective effects of geniposide remain to be fully established.…”
mentioning
confidence: 99%
“…9) Our previous works showed that geniposide was a novel agonist for glucagon-like peptide 1 receptor (GLP-1R), which induced the neuronal differentiation of PC12 cells and prevented PC12 cells from oxidative stress. [10][11][12] However, the mechanisms involved in these cytoprotective effects of geniposide remain to be fully established.…”
mentioning
confidence: 99%
“…A significant increase on the GAP-43 protein level in parallel with neurite outgrowth was observed after the treatment with geniposide. The data also demonstrate that geniposide induces the neuronal differentiation of PC12 cells via the MAPK pathway (Liu et al, 2006). Therefore, geniposide has neuroprotective effects due to the activation of GLP-1R in cells without nNOS.…”
Section: Neurite Outgrowth Promoted By Geniposidementioning
confidence: 57%
“…Its protective effect from memory impairment and the normalization of objection recognition has been shown in animal behavioral experiments (Gao et al, 2014;Lv et al, 2014). Using a high-throughput screen for GLP-1R agonists, geniposide was identified as an agonist for GLP-1R (Liu et al, 2006). It has been shown that the activation of GLP-1R by geniposide induces neurotrophic and neuroprotective effects in cells .…”
Section: Introductionmentioning
confidence: 98%
“…In several neuronal cell line studies, GLP‐1 induced neurite outgrowth24, 25. One study found that ICV infusion of GIP stimulated progenitor cell proliferation in the rat hippocampus26.…”
Section: Biology Of Incretin Hormones In Peripheral Organs and The Brainmentioning
confidence: 99%